Addressing suicide risk in partners and relatives bereaved by suicide. (20th March 2018) - Pitman, Alexandra
Summary: Analyses of population-based registers provide evidence to support an increased risk of suicide and mental illness after the suicide of a relative or partner. This editorial explores the implications of this work for progressing recommendations made in suicide prevention strategies regarding the specific support provided to people bereaved by suicide. Declaration of interest: A.P. served on the Public Health England expert reference committee contributing to local guidance on commissioning and delivering postvention support (Public Health England, 2016. Support After a Suicide: A Guide to Providing Local Services ) and has submitted applications for funding to investigate mediators of suicide risk after suicide bereavement. Since writing this article she has become a Patron of the Support After Suicide Partnership.